Cerebellar degeneration in primary Sjögren syndrome: a case report - Chuah, Seow Lin; Ahmad Tirmizi, Jobli; Sharifah Aishah, Wan; Teh, Cheng Lay (Springer Nature, 2021)
Background Cerebellar degeneration is a rare and severe presentation of primary Sjögren syndrome. There are few case reports of cerebellar degeneration associated with different autoimmune diseases, especially with systemic lupus erythematosus and neuro-Behcet’s disease. There are only six patients reported worldwide to be affected by cerebellar atrophy associated with primary Sjögren syndrome. In this report, we describe a patient with primary Sjögren syndrome who presented with ataxia due to cerebellar degeneration.